Pengembangan Modul IPA Terpadu Terintegrasi Ayat-Ayat Al-Qur’an Pada Materi Air Sebagai Sumber Kehidupan - Latifah, Sri (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2015)
This research is a development research that aims to produce Interated IPA module product integrated with Al-Qur'an verses on the material of Water as the source of life, as a teaching material of students of SMP / MTs class VII. The problems in this study include how to develop Integrated IPA module integrated with Qur'anic verses on the material of Water as the Source of Life, and whether the Integrated IPA module development integrated with Qur'anic verses on the material of Water as the Source of Life is interesting to be used as teaching materials. This research is a development research using Research and Development research method (R & D). The resulting product is categorized very good based on validation from material experts with 85% percentage and design expert with 85% score, and module is very interesting to be used as a teaching material based on teacher's assessment to get 86% score percentage, and students’ response on small group test obtained the percentage of 76% and field trials received a score percentage of 81%.Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk menghasilkan produk berupa modul IPA Terpadu terintegrasi ayat-ayat Al-Qur’an pada materi Air Sebagai Sumber Kehidupan sebagai bahan ajar siswa SMP/MTs kelas VII. Masalah pada penelitian ini antara lain, bagaimana mengembangkan modul IPA Terpadu terintegrasi ayat-ayat Al-Qur’an pada materi Air Sebagai Sumber Kehidupan, dan apakah pengembangan modul IPA Terpadu terintegrasi ayat-ayat Al-Qur’an pada materi Air Sebagai Sumber Kehidupan menarik untuk dijadikan sebagai bahan ajar. Penelitian ini merupakan penelitian pengembangan menggunakan metode penelitian Research and Development (R & D). Produk yang dihasilkan terkategori sangat baik berdasarkan validasi dari ahli materi dengan presentase skor 85% dan ahli desain dengan skor 85%, serta modul sangat menarik untuk dijadikan bahan ajar berdasarkan penilaian guru memperoleh presentase skor 86%, dan respon siswa pada uji coba kelompok kecil memperoleh persentase 76% serta uji coba lapangan memperoleh presentase skor 81%.